2003
DOI: 10.2172/809607
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Feasibility of Applying Used EV Batteries in Stationary Applications

Abstract: The technical and economic feasibility of applying used electric vehicle (EV) batteries in stationary applications was evaluated in this study. In addition to identifying possible barriers to EV battery reuse, steps needed to prepare the used EV batteries for a second application were also considered. Costs of acquiring, testing, and reconfiguring the used EV batteries were estimated. Eight potential stationary applications were identified and described in terms of power, energy, and duty cycle requirements. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
117
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 0 publications
0
117
0
1
Order By: Relevance
“…Analyses of spinning reserve feasibility have shown mixed results, however. A study by Cready et al showed that costs incurred from spinning reserves were higher than potential revenue, while another study by Kempton et al found most vehicle batteries would be profitable with spinning reserves [11], [22]. Moura concluded that EDVs are unappealing for spinning reserves, but Sioshansi et al…”
Section: Spinning Reservesmentioning
confidence: 99%
See 4 more Smart Citations
“…Analyses of spinning reserve feasibility have shown mixed results, however. A study by Cready et al showed that costs incurred from spinning reserves were higher than potential revenue, while another study by Kempton et al found most vehicle batteries would be profitable with spinning reserves [11], [22]. Moura concluded that EDVs are unappealing for spinning reserves, but Sioshansi et al…”
Section: Spinning Reservesmentioning
confidence: 99%
“…Because it is inherently a quick-response market (generators must respond to the command signal sent every 2-4 seconds), it is intuitive that a battery system would be a superior candidate for this market in particular [7], [11]. Furthermore, regulation services account for 80% of the A/S expenditures by the Independent System Operator (ISO); it is a much larger and more valuable market than spinning reserves [6], [7], [22].…”
Section: Frequency Regulationmentioning
confidence: 99%
See 3 more Smart Citations